Potential for the Development of User Innovation by Salespersons in Stores - Nobutoshi Shimizu (Maketingu Janaru, 2019)
Many Japanese retailers consider that the development of unique own-brand products is important in the current fierce competition between retailers. In previous research, the volume of sales and consumer information generated at each store have become the main sources of attractive product development by retailers, which tend to be inferior to manufacturers with respect to the capacity for product development. In addition, this article discusses the potential of user innovation developed by salespersons in stores. On the assumption that many lead users are embedded among the retailers as salespersons, two case studies were conducted focusing on the chain store retailers of sports gear and grocery supermarkets. We showed that the existence of new product development outcomes can be obtained through lead users (i.e., salespersons), and also that there is effective activity of user innovation through another type of management, crowdsourcing from salesperson at stores. This article suggests that utilization of user innovation contributes to effective product development outcomes for many retailers.